1994
DOI: 10.1159/000159033
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Isoform Expression in Smooth Muscle Cells during Physiological and Pathological Vascular Remodeling

Abstract: There is substantial evidence indicating that the study of cytoskeletal and cytocontractile protein composition in vascular smooth muscle cells (SMCs) can be valuable in tracing structural changes during vascular remodeling. Recent nucleic acid and protein investigations suggest that myosin can be used as a new specific marker for the identification of SMC phenotypes in some pathological conditions affecting the vascular wall. In view of this new information, it would seem timely to review the structural bases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 146 publications
(253 reference statements)
4
38
0
1
Order By: Relevance
“…VSMCs express two contractile-type isoforms of SM-MHCs (SM1 and SM2) and two synthetic types of NMHC isoforms (NMHC-B/SMemb and NMHC-A) (9,13). Our findings on the localization of SM-MHCs and NMHCs in the hearts of WKY and SHR agreed with the previous results (15,16), indicating that neither NMHC-A nor NMHC-B/SMemb was a …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…VSMCs express two contractile-type isoforms of SM-MHCs (SM1 and SM2) and two synthetic types of NMHC isoforms (NMHC-B/SMemb and NMHC-A) (9,13). Our findings on the localization of SM-MHCs and NMHCs in the hearts of WKY and SHR agreed with the previous results (15,16), indicating that neither NMHC-A nor NMHC-B/SMemb was a …”
Section: Discussionsupporting
confidence: 90%
“…Based on the results of the specific localization of SM1, SM2, and GATA-6 in the intramyocardial arteries, we demonstrated that 20-week-old SHR showed a significant phenotypic change of SMCs in the intramyocardial arteries towards the synthetic type compared with 20-week-old WKY. Our results for the phenotypic change of SMCs in the hearts were similar to those reported previously, since VSMCs have been shown to modulate their state of differentiation in response to the activation of the local reninAng system, and this plays a crucial role in proliferation and vascular remodeling in hypertension (4,5,9). In addition, VSMCs from SHR produce Ang II and express phenotypic change toward the synthetic type more than those from WKY, which are independent of hypertension (18,19).…”
Section: Fig 1 Confocal Microscopic Analyses Of the Localization Ofsupporting
confidence: 89%
See 2 more Smart Citations
“…Maintenance of this contractile phenotype in cultured smooth muscle cells is dependent upon a number of carefully controlled cell culture conditions, specifically cell density, avoidance of foetal bovine serum exposure and a requirement for heparin [14,33]. Although modulation of the contractile phenotype and its role in systemic vascular disease is the subject of intense research by vascular biologists [34,35], little attention has been paid so far to its occurrence in airway disease, although some investigators have drawn parallels in the mechanisms for vascular and airway remodelling [26,27,36]. Nevertheless, there is increasing acceptance that, in primary culture, exposure of airway smooth muscle cells to a mitogenic stimulus (e.g.…”
Section: Heterogeneity and Phenotypic Modulation Of Airway Smooth Musclementioning
confidence: 99%